2022
DOI: 10.1021/acs.jafc.2c00809
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Peptides from Lupin (Lupinus angustifolius) Prevent the Early Stages of Atherosclerosis in Western Diet-Fed ApoE–/– Mice

Abstract: We have previously reported the in vitro hypocholesterolemic, anti-inflammatory, and antioxidant effects of Alcalasegenerated lupin protein hydrolysate (LPH). Given that lipoprotein deposition, oxidative stress, and inflammation are the main components of atherogenesis, we characterized the LPH composition, in silico identified LPH−peptides with activities related to atherosclerosis, and evaluated the in vivo LPH effects on atherosclerosis risk factors in a mouse model of atherosclerosis. After 15 min of Alcal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…In this sense, an increase in the activity of antioxidant enzymes was observed previously in plasma and liver of mice treated with LPH. [10,36] Interestingly, a previous study using the same mouse model has shown an anxiolytic role of LPH treatment. [12] Therefore, we suggest that the antioxidant effects observed in the CNS of LPHtreated mice could be a possible explanation for the previous anxiolytic effects demonstrated.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In this sense, an increase in the activity of antioxidant enzymes was observed previously in plasma and liver of mice treated with LPH. [10,36] Interestingly, a previous study using the same mouse model has shown an anxiolytic role of LPH treatment. [12] Therefore, we suggest that the antioxidant effects observed in the CNS of LPHtreated mice could be a possible explanation for the previous anxiolytic effects demonstrated.…”
Section: Discussionmentioning
confidence: 90%
“…[25] In this line, a previous study by our group demonstrated that LPH is rich in the amino acids Leu, Val, Pro, His, Thr, Tyr, and Phe. [9] Other food-derived hydrolysates generated with Alcalase have shown potent antioxidant effects, such as pea, corn, soy, zein, amaranth, and rice bran protein hydrolysates. [26][27][28][29][30] Furthermore, numerous scientific articles have shown that hydrolysates obtained from Alcalase have greater antioxidant effects than hydrolysates generated with other proteases such as protamex, neutrase, flavourzyme, papain, and pepsin.…”
Section: Discussionmentioning
confidence: 99%
“…23 In addition, a recent study supports the pleiotropic effects of a lupin bioactive peptide-based functional food on the critical steps of atherosclerosis, including inflammation, oxidative stress, and cholesterol metabolism. 24 Recently, we have demonstrated that the lupin protein hydrolysate (LPH) obtained after the hydrolysis with Alcalase® reduces hepatic steatosis and abdominal adiposity, as well as total cholesterol levels in apolipoprotein E-deficient (ApoE −/− ) mice. Furthermore, the LPH increases the hepatic total antioxidant capacity and reduces the hepatic inflammatory status in these mice.…”
Section: Introductionmentioning
confidence: 99%
“…23 In addition, a recent study supports the pleiotropic effects of a lupin bioactive peptide-based functional food on the critical steps of atherosclerosis, including inflammation, oxidative stress, and cholesterol metabolism. 24…”
Section: Introductionmentioning
confidence: 99%
“…The proteins are suitable for the preparation of gluten-free foods for coeliac persons [ 8 ], and the protein isolates have desirable physical, technological, and functional properties, such as foaming, gelling, emulsifying, and water absorptive capacities [ 7 , 9 , 10 ]. Additionally, lupin protein hydrolysates showed promising health properties as anxiolytic [ 11 ], as nutraceutical able to prevent the early stages of atherosclerosis [ 12 ], as functional ingredients in foods for diabetic people [ 13 ], etc.…”
Section: Introductionmentioning
confidence: 99%